IMPROVING STUDENTS’ SPEAKING ABILITY BY USING INFORMATION GAP METHOD - Harisa Dwi Oktira (XXXXXXXX, 2022)
This research aimed to find out the improvement of students’ speaking ability by using the information gap method. The subjects of research were the students in grade X MIA-1, which consists of 36 students in the class. This research was conducted by using Classroom Action Research by Kemmis and McTaggart, which consisted of two cycles. The first was qualitative data that was obtained from observation, interviews, diary notes, and documentation that was analyzed using the Miles and Huberman technique. The quantitative data were obtained from a speaking test and were analyzed using the mean and percentage scores. The result of this research showed that the students’ speaking abilities improved after using the information gap method. The students have more participation and are active in conveying their ideas, opinions, and feelings during the process of speaking activity. Moreover, the students’ scores were higher than before after implementing the method. It can be shown from the result of the pre-test, post-test 1, and post-test 2, which are in the pre-test, that the students‘ mean score was 62, which only 6 students, or 16.6% of the 30 students who passed the minimum passing grade. In post-test I, the mean student's score was 72, in which there were 17 students, or 47%, who passed the minimum passing grade. At last, the mean score of students in post-test 2 was 76, meaning that 29 students, or 80%, passed the minimum passing grade. It indicated that the information gap method can improve students’ speaking ability.  Keywords: Speaking ability, information gap method, classroom action research.